Differential MicroRNA Expression Pattern in Endothelial Progenitor Cells During Diabetic Retinopathy - Shi, Ze-Hui; Han, Xiao-Yan; Yao, Mu-Di; Liu, Chang; Jiang, Qin; Yan, Biao (Frontiers in Cell and Developmental Biology, 2021)
Endothelial progenitor cells (EPCs) are involved in the pathogenesis of microvascular dysfunction in diabetic retinopathy (DR). MicroRNAs (miRNAs) served as crucial regulators in many biological process and human diseases. Herein, to investigate the expression profile and possible role of miRNAs in EPCs, small RNA sequencing was conducted to identify EPC dysfunction-related miRNAs in DR. A total of 72 miRNAs were differentially expressed in EPCs following high glucose stress. Based on GO analysis, the target genes of differentially expressed miRNAs were targeted to “protein binding”, “cell differentiation” and “cytoskeleton”. KEGG pathway analysis revealed that cGMP-PKG signaling pathway was tightly associated with miRNA-mediated EPC function. Furthermore, miR-375-3p was verified to be up-regulated in the clinical samples of DR patients. Inhibition of miR-375-3p protected against hyperglycemic stress- or hypoxic stress-induced EPC injury, which increased the viability, proliferation, migration, and tube formation ability of EPCs and retarded the development of apoptosis. Collectively, this study provides a novel insight into the pathogenesis of EPC dysfunction in DR. miR-375-3p is a potential target for the diagnosis or treatment of DR.